A Model of Nominal Contracts - Smith, Bruce D. (Journal of Labor Economics, 1989)
A model is produced in which labor contracts that prespecify (unindexed) nominal wage payments arise endogenously. These contracts function as a self-selection mechanism. Under appropriately different attitudes toward price-level risk (which can either arise directly from preferences or be induced by different patterns of asset holdings), nominal contracts allow high-productivity workers to signal their type by their willingness to accept unindexed contracts. This explanation of nominal contracts does not require that money be used in any particular set of transactions, and nominal contracts enhance the risk faced by all parties accepting them.